PENGGUNAAN KATALIS ZnO-H2O2 UNTUK DEGRADASI ZAT WARNA RHODAMIN B DAN ALIZARIN-S - Safni -; Fitrah Amelia; Oktanora Liansari; Hamzar Suyani; Yulizar Yusuf (Jurnal Riset Kimia, 2009)
ABSTRACT The textile industry produce colored waste liquid that can contaminate the line water and its populations. A number of dyes are using in textile industry processes such as rhodamine-B and alizarine-S. Both of dyes are toxic for human life. In order to reduce the concentration that dyes is used the sonolysis method which have good efficiency and effective to degrade this pollutants. Sonolysis was performed using an ultrasound energy at 47 kHz. Catalyst ZnO is used to get better degradation. Rhodamine-B 2mg/L with 0.3 g ZnO addition, pH 5, temperature 40°C get 35.44% degradation after 60 minutes. If we used 3 mL H2O2 30% in the same condition the degradation up to 42.67% and with the combination of 0.3 g ZnO - 3 mL H2O2 as catalysts it got 91.99% after 90 minutes. Alizarine-S 20 mg/L with 0.5 g ZnO addition, pH 5, temperature 50°C was degraded up to 86.45% after 35 minutes. Furthermore, the degradation reached 95.79% if it used 0.5 g ZnO and 25 mL H2O2 30% at pH 5 and temperature 50°C after 35 minutes sonolysis. Keywords : rhodamine-B, alizarine-s, ZnO, H2O2